Strategi Komunikasi Divisi Humas Kementerian dalam Negeri dalam Menanggapi Gelombang Demonstrasi Mahasiswa dan Masyarakat pada September 2025 - Nazwa Rivie Azahra; Hudi Santoso (Jurnal Riset Rumpun Seni, Desain dan Media, 2025)
The study explores the communication strategy of the Public Relations Division of the Ministry of Home Affairs (Kemendagri) in responding to the wave of student and community demonstrations in early September 2025. This research aims to identify the strategic approach and challenges faced by the division in managing public communication during a national socio-political crisis. Using a qualitative descriptive method through observation, participation, and in-depth interviews with two informants from the division, the study reveals that Kemendagri’s communication strategy emphasized transparency, cross-institutional coordination, and the empowerment of local governments to maintain stability. The division also adopted multi-channel communication, including social media, press releases, and press conferences, ensuring message consistency and public reassurance. However, several challenges were identified, such as the sensitivity of political issues, the spread of misinformation and hoaxes, limited human resources, and the suboptimal implementation of two-way communication. The findings indicate that public communication during a crisis requires accuracy, empathy, and collaboration across institutions. This study implies that strengthening transparency, enhancing crisis communication skills, and improving digital responsiveness are essential for the Ministry’s public relations performance in future crises.